Enrichment characteristics and genesis mechanism of critical elements (Nb-Ta-Zr-Hf-REE-Y) in coals: a case study of Late Permian coalfield in Northeastern Guizhou, China - Ziyi Ye; Baoqing Li; Jialiang Cao (Frontiers in Earth Science)
The discovery of coal-type beneficial metal deposits and corresponding genesis mechanisms are cutting-edge issues in current sedimentary environment research. Based on industrial analysis, mineralogy, and geochemical measurement of seven typical mines in the Late Permian coalfield of northeastern Guizhou, the enrichment characteristics and mineralization mechanisms of critical metal elements in coal rocks have been revealed in this study. The chemical composition of coal from the Late Permian Wujiaping Formation in northeastern Guizhou is mainly characterized by ultra-low moisture content, medium ash and medium volatile matter yield, and medium high sulfur content. The content of coal-hosted critical metal elements is very high. There are significant differences in elemental composition of coalbeds from different mines, and they are mostly enriched vertically in the coal between and near tonsteins. For example, the K1 coalbed of XX Mine is characterized by Se-Nb-Ta-Zr-Hf enrichment, while the K3 coalbed only has Se enrichment characteristics. TDY Mine has the characteristics of Zr-Nb-Be-Se-Hf-Ta and rare earth element (REE) -Y enrichment. The differences in assemblage type and abundance of critical metal elements in coal rock are mainly controlled by the input of terrestrial detrital materials, environmental conditions, seawater, and hydrothermal fluids. The weathering products of acidic volcanic ash, basalt, and intermediate acidic rocks in the Kangdian Upland provide material sources for the enrichment of critical metal elements. Specifically, the input of intermediate acidic volcanic ash is the main factor for the enrichment of Nb-Ta-Zr-Hf-REY (REE plus Y) in most coal mines. The coastal swamp environment in marine-continental transitional zone, periodic seawater transgression, and hydrothermal fluids control the alteration, transformation, and formation of detrital minerals, affecting the activation and migration of some critical metal elements.